Investigation of the gradation effect on ballast mechanical behaviors by means of discrete element modeling - part 2. (October 2019) - Wang, B; Martin, U; Rapp, S; Schuk, V
Abstract: The ballast gradation has a strong influence on the mechanical behaviour of ballast aggregates. Discrete Element Method (DEM) based simulations are performed to investigate the gradation effect of ballast aggregates on their settlement, ballast position rearrangement, breakage rate and void ratio. In the second part of this article, DEM based simulations are performed to investigate the gradation effect of ballast aggregates on their settlement, ballast position rearrangement, breakage rate and void ratio (Part 2). The results indicate that the settlement and the ballast position rearrangement increase with the decrease of the averaged ballast size of a ballast aggregate, whereas the void ratio decreases. Besides, the breakage and the ballast position rearrangement occur mainly with the dynamic loading rather than the static loading. Based on the simulation result, appropriately enlarged ballast stones will benefit not only the stability, but also the hydraulic conductivity of ballast aggregates. The gained result can be used for the optimization of ballast aggregate regarding to its gradation, so that its service cycle can be prolonged.